Oil Price Fluctuations and Stock Price Volatility in Southeast Asian Stock Markets - Ng, Yuen Yein (2015)
Recently substantial amount of studies in understanding the nature of oil price and stock market have been evolving rapidly but the examination of differential effect between spot and futures oil prices on stock returns within certain periods are limited. Extending earlier work in the literature, we conduct a study with the monthly data of Dated Brent crude oil prices and stock indices in the six main Southeast Asian equity markets to investigate. There are three main objectives in this study. Firstly this study aims to identify whether different stages of 2008 Global financial crisis (pre, during and post) will influence the impact brought by oil prices on stock returns in Southeast Asian equity markets. In addition, impacts brought by oil futures prices on the stock returns will be tested. Moreover, we want to determine the relationship between oil prices and stock returns when pooling all the time series observations across a variety of cross-sectional Southeast Asian country markets. Under APT multi-factor model of asset pricing, oil prices can explain variations in oil returns. Under cost and carry relationship, both spot and futures oil prices should bring similar impact on stock returns. Also, occurrence of financial crisis leads to contagion effect among the countries. Under the assumption of high volatility during crisis period, we investigate whether oil prices are highly volatile during crisis period and consequently affect the stock market returns using both GARCH (1, 1) and Panel GARCH models. Our major findings suggest that oil prices will bring different impact on stock returns in Southeast Asian equity markets across different stages of 2008 Global financial crisis. When economy recovers from the recession period, higher oil demand leads the oil prices in stock markets from oil-exporting countries to increase. Furthermore, the impact on stock returns exerted by oil futures prices is different from oil spot prices in the period of before and during financial crisis periods due to the divergence of spot oil prices from futures oil prices. Furthermore, we find out that Indonesia, Malaysia, Philippines and Thailand show similar responses towards the oil prices information when pooling all the news and information in cross-sectional Southeast Asian country markets. This reflects the existence of contagion effect. We suggest that policy makers should always observe and maintain the movement of both spot and futures oil prices to avoid the excessive futures market volatility. Investors can invest in oil-exporting countries or other countries which are rich in commodities during the recovering period of financial crisis. Overall, this study has contributed in the oil research area.